(untitled) (Revista Ifes Ciência, 2025)
The concrete used in prestressed slabs in Greater Vitória, Espírito Santo, Brazil, usually contains PC type III (blast furnace slag Portland cement) (ABNT, 2018) and PC type V High Early Strength (Portland cement V ARI) (ABNT, 2018), facilitating faster execution of protension. The aim of this study is to analyze the behavior of concretes with PC III and PC ARI in their composition with up to 182 days of age. In order to do so, two types of concrete were manufactured: the reference one - containing only PC III - and the other one in which 30% of PC III was substituted by PC ARI. By analyzing the concretes' strength to axial compression at the 7th day, we observed that the concrete with substitution displayed a resistance to axial compression that is 28.2% higher than the reference concrete. Meanwhile, at 91 days of age, the reference concrete displayed an axial compression that was 7.6% higher than the concrete with substitution. Therefore, we notice a significant change in the behavior of concrete composed of cement with high early strength (PC ARI).